THE ROLE OF WORK MOTIVATION AS MEDIATING VARIABLE ON THE RELATIONSHIP BETWEEN LEADERSHIP STYLES AND JOB SATISFACTION: EMPIRICAL INVESTIGATION AT REGIONAL DISTRICT OFFICE, BENGKULU PROVINCE - Nova Delastri; Fahrudin Js Pareke (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
Current problem that often take place in the public sector is on how to improve employeeperformance. Employee performance will not be far from the three variables that examined in thisstudy such as leadership style, work motivation and job satisfaction. Research conducted at theRegional Office Bengkulu Province. The purpose of this current research is to examine the effectof leadership style on work motivation and job satisfaction. In addition, the research aims to knowthe role of work motivation in mediating the relationship between leadership style and jobsatisfaction. Mediated Regression Analysis (MRA) applied to answer the research problems. Inthe first step data analysis, the effect of leadership style on work motivation was tested, followedby testing of the effect of leadership style on job satisfaction at the next step. The effect of workmotivation on job satisfaction was also tested, followed by test the role of work motivation as themediating variable as well. Result concluded that each independent variable has significant effecton dependent variable. Furthermore, result also proved that motivation served as a mediating rolein affecting the relationship between leadership style and job satisfaction. Based on researchresults, efforts to increase job satisfaction through leadership style cannot ignore the motivationalaspect of work. The results are also implied that efforts to achieve employee satisfaction shouldconsider the elements that can improve employee motivation, to increase the performance.Key Words: Work Motivation; Leadership Style; Job Satisfaction